2019
DOI: 10.1016/j.jgr.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and subchronic toxicological study of a novel ginsenoside derivative 25-OCH3-PPD in beagle dogs

Abstract: BackgroundGinsenosides have been widely used clinically for many years and were regarded as very safe. However, a few researches on the toxicities of these kinds of agents showed that some ginsenosides may have side-effect on the rats or dogs. So it is extremely necessary to further clarify the potential toxicity of ginsenosides. This study was carried out to investigate long-term toxicity and genotoxicity of 25-methoxydammarane-3, 12, 20-triol (25-OCH3-PPD), a new derivative of ginsenoside, in beagle dogs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…In a beagle toxicity study, animals in the 36 mg/kg group showed reversible hepatotoxicity and significant weight loss during the study period. Animals in the 4 and 12 mg/kg groups did not show any significant toxicity (61).…”
Section: Biotransformation Pharmacokinetics and Safety Of Ckmentioning
confidence: 84%
“…In a beagle toxicity study, animals in the 36 mg/kg group showed reversible hepatotoxicity and significant weight loss during the study period. Animals in the 4 and 12 mg/kg groups did not show any significant toxicity (61).…”
Section: Biotransformation Pharmacokinetics and Safety Of Ckmentioning
confidence: 84%
“…During a beagle toxicity investigation, dogs in the 36 mg/kg group experienced considerable weight loss and reversible hepatotoxicity. There was no discernible toxicity in the animals in the 4 and 12 mg/kg groups [ 39 ]. Table 2 elucidated the cytotoxicity of CK on different cell lines.…”
Section: Pharmacokinetics Safety and Toxicological Studies Of Ck And ...mentioning
confidence: 99%
“…CK has been shown to have antidiabetic, antitumor, anti-inflammatory, and hepatoprotective activities [ 23 ]. A new derivative of ginsenoside from P. notoginseng , 25-OCH 3 -PPD, not only inhibited various types of cancer cell lines, such as pancreatic, breast, and lung cancer, but also exhibited nongenotoxic properties for antitumor treatment [ 24 ]. Noticeably, differences in the position of sugar linkers and hydroxyl groups give direction to biological activities.…”
Section: Ginsenosides: Classification and Cell Biological Mechanism I...mentioning
confidence: 99%
“…Furthermore, CK shows the ability to inhibit and migrate human glioblastoma U87MG and U373MG cells via an arrested cell cycle progression at the G0/G1 phase [ 23 ]. Moreover, 25-OCH 3 -PPD has significant effects on decreasing the survival and inhibiting the proliferation of human prostate and breast cancer cell lines [ 24 ]. Thus, ginsenosides likely have therapeutic potential for the treatment of various cancer diseases.…”
Section: Ginsenosides: Classification and Cell Biological Mechanism I...mentioning
confidence: 99%